2015
DOI: 10.1155/2015/202059
|View full text |Cite
|
Sign up to set email alerts
|

Urethrovaginal Fistula in a 5-Year-Old Girl

Abstract: Urethral fistulas are rare in girls. They occur most of the time during trauma. The case presented here is an iatrogenic fistula. The treatment was simple and consisted of a simple dissection and suture of urethra and vagina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 10 publications
(20 reference statements)
3
6
0
Order By: Relevance
“…Our patients had history of FGM with is consistent with what was reported by Kiosoglous, et al [2], Webster, et al [3], Meeks, et al [4], and Coulibaly et al [11]. They reported that urethrovaginal fistula in girls can be congenital or post traumatic.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our patients had history of FGM with is consistent with what was reported by Kiosoglous, et al [2], Webster, et al [3], Meeks, et al [4], and Coulibaly et al [11]. They reported that urethrovaginal fistula in girls can be congenital or post traumatic.…”
Section: Discussionsupporting
confidence: 90%
“…The age of patients of 12 years is higher than the average age reported for FGM of 5-8 years [7]. Coulibaly and Sangare [11]reported 5-year-old girl with urethrovaginal fistula which was suspected to be post traumatic as the traumatic event was not obvious.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations